First experience with the Edwards SAPIEN transcatheter aortic valve implantation (TAVI). Data from the Western Cape, South Africa - Weich, Hellmuth; Mabin, Tom; van Wyk, Jacques; van Zyl, Wynand; Vivier, Rocco; Phillips, Andre; van Gruene, Ronel (SA Heart Journal, 2017)
Background: Transcatheter aortic valve implantation (TAVI) is an exciting new technology that was launched in South Africa in October 2009 for the treatment of aortic stenosis in patients at high risk for conventional surgery. We report our initial experience with TAVI in the Western Cape, South Africa. Methods: 70 patients with severe symptomatic aortic stenosis underwent TAVI with the Edwards SAPIEN device (26 via transapical approach and 44 via transfemoral) at Panorama and Vergelegen Mediclinic hospitals in the Western Cape. All implants were performed by a team consisting of 2 cardiothoracic anaesthesiologists, 2 cardiothoracic surgeons, 2 cardiologists and an echo expert. Results: Patients were at high risk with a mean age of 80 years and a mean logistic EuroSCORE of 26. The acute procedural success rate was 97% with two acute deaths. At 30 days, there were a total of 5 deaths. Major vascular complications were seen in 6 cases (9%). Only one stroke was seen during the follow-up period. Conclusions: With a multidisciplinary team approach and careful patient selection, TAVI can be performed by a high volume centre in South Africa with results comparable to international published outcomes.